How People with Dementia and their Carers Adapt their Homes. A Qualitative Study. (April 2019) - Allen, Frances; Cain, Rebecca; Meyer, Caroline
The objective was to explore the ways in which people with dementia and their carers adapt their homes, including the barriers and use of available information. Semi-structured interviews were conducted with 10 people with dementia and their informal carer. The collected data were analysed using thematic analysis. Three core themes emerged: Maintaining familiarity and coping with change, Having knowledge and finding knowledge and Meeting challenges through home adaptation . The most significant barriers to making home adaptations were lack of knowledge and maintaining familiarity. Having more information and making home modifications earlier might enable individuals with dementia to adjust to their adapted environment.